Managerial economics principles and worldwide applications - Salvatore, Dominick; Salvatore, Dominick; Rastogi, Siddhartha K. (Oxford University Press, 2016)
Reflecting the highly globalized nature of tastes, production, labour markets, and financial markets in today's world, this book presents the theory of the firm as a unifying theme to examine the managerial decision-making process. Adopting a global perspective, it synthesizes economic theory, decision science, and business administration studies, examining how they interact as a firm strives to reach optimal profitability and efficiency in the face of modern constraints.